Pengungkapan Sustainability Report Pada Perusahaan Sub Sektor Perbankan Di Indonesia - Yusuf Faisal; Pebriyanti Palentina; Jihan Maharani (Program Studi Akuntansi Sekolah Tinggi Ilmu Ekonomi Tri Bhakti, 2023)
Purpose – This study aims to determine the effect of Company Size, Profitability, Liquidity and Leverage on Sustainability Report Disclosure in Banking Sub-Sector Companies Listed on the Indonesia Stock Exchange (BEI) in 2017-2022. Design/methodology/approach – This study uses a type of quantitative research. This research was conducted by observing financial sector companies listed on the Indonesia Stock Exchange (IDX) totaling 47 companies. The data source used is the company's annual report from 2017-2022. To get the results of this study, researchers used Eviews12. Findings – The results of this study indicate that Company Size has a positive and statistically significant effect on Sustainability Report Disclosure, Profitability has a positive and statistically significant effect on Sustainability Report Disclosure, Liquidity has a negative and statistically insignificant effect on Sustainability Report Disclosure, and Leverage has a negative and statistically insignificant effect on Sustainability Report Disclosure. Research limitations/implications – This study discusses the Disclosure of Sustainability Reports and the factors that influence it in Banking sub-sector companies, namely Company Size, Profitability, Liquidity, and Leverage in Banking Sub-Sector Companies Listed on the Indonesia Stock Exchange (IDX).